Nontraditional Aldol Condensation Performance of Highly Efficient and Reusable Cs+ Single Sites in β‑Zeolite Channels - Ghosh, Shilpi; Acharyya, Shankha S; Yoshida, Yusuke; Kaneko, Takuma; Iwasawa, Yasuhiro; Sasaki, Takehiko (ACS applied materials & interfaces, 2022)
Aldol reactions (self- and cross-aldol condensations) for conjugated enone synthesis were efficiently performed on large-sized Cs+ single sites (1 wt %) confined in β-zeolite channels in toluene, which showed the highest level of catalytic aldol condensation activity among reported zeolite catalysts. In general, aldol condensation reactions for C–C bond synthesis can proceed by acids (e.g., H+), bases (e.g., OH–), enolate species, and acidic or basic solid catalysts. However, the Cs+ single site/β sample without significant acid–base property showed unprecedented, efficient, and reusable catalysis for self-aldol and cross-aldol condensations. Intrinsically inactive Cs+ single sites due to the noble-gas electronic structure were transformed to active Cs+ single sites in β-zeolite channels. Cs+/β has many advantages such as broad substrate scope, eco-friendliness, high product selectivity and yield, and simple work-up procedure. Thus, the Cs+ single site/β provides an attractive and useful methodology for practical C–C bond synthesis. On the basis of the Cs+/β characterization by X-ray photoelectron spectroscopy (XPS), in situ X-ray absorption fine structure (XAFS) (X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS)), and temperature-programmed desorption (TPD), density functional theory (DFT) calculations of the self- and cross-aldol condensation reaction pathways involving the transition states on the Cs+ single site in β-zeolite channel revealed nontraditional concerted interligand bond rearrangement mechanisms.